Recovery of the Decorin-Enriched Fraction, Extract (D), From Human Skin: An Accelerated Protocol. Issue 4 (30th September 2004) - Wheatley, Denys N.; Graham, Emma; McMaster, R. Shannon; Muir, Ian F. K.; Holmes, John D.; Davies, Michaela
Abstract : The original extraction procedure of Engel and Catchpole [1] has often been used to recover decorin-enriched material from the skin. This material has a strong inhibitory effect on fibroblast proliferation, and clearly suppresses it in skin except after the first 5–6 days of wounding when new scaffold material is required. The aim of our present study has been to find and evaluate the product of a faster recovery method, and to check its consistency as a more reliable means of regularly obtaining sufficient material for topical application in wounds that might become hypertrophic. Modifications of the original Toole and Lowther [2] extraction procedure have been carefully evaluated in an attempt to cut preparation time without compromising biological activity of the inhibitory extract. We have devised a faster recovery procedure without compromising biological activity, even if initial recovery has been somewhat reduced. The latter problem could be offset by repeated cycles of the final extraction step. The main inhibitory activity is shown to be within the decorin-enriched "extract D, " as the core protein and DSPG II. Adjustment of the extract towards neutrality after dialysis against water keeps most of the extracted protein in solution and yielded a decorin-enriched preparation that had a specific activity equivalent to that of the old method. It also yielded a fraction that was readily lyophilised to give a small amount of material that could be stored indefinitely without loss of activity and readily redissolved in aqueous solution. A reliable and relatively quick method is presented for the production, from human skin, of a decorin-enriched preparation that has strong fibroblast inhibitory action. The value of the procedure is that it is inexpensive and can produce the quantities that might be used topically in reducing hypertrophic scarring of wounds.